REVITALISASI AKSARA JAWA MELALUI GAMAN RAJA - agung vendi setyawan (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
Early introduction through activities to color Javanese script and habituation to writing Javanese script according to the correct flow and technique is a real action to revitalize Javanese script. Javanese script is an Indonesian script and one of the elements in regional languages. Preserving Javanese script means caring for Javanese cultural assets that encourage the creation of various forms of expression to enrich the culture of the Indonesian nation. The development of Javanese script teaching materials is a form of revitalizing regional languages and advancing cultural objects in the language sector. Gladhi Maca and Nulis Aksara Jawa (Gaman Raja) is the development of teaching materials for reading and writing Javanese script, especially for students at the elementary school (SD) level. Gaman Raja consists of two volumes, namely Volume 1 Reading and Coloring Javanese Script and Volume 2 Reading and Writing the Beginning of Javanese Script. Gaman Raja volume 1 aims to introduce the forms of Javanese script through the activity of coloring pictures of Javanese script. The benefits can be as a means of recreation and training fine motor skills. Gaman Raja Volume 2 aims to practice writing Javanese script according to the correct rules. Media Gaman Raja is included in the very feasible category based on media assessment results, namely 85% from media expert validator I and 90% from media expert validator II. The Gaman Raja material is included in the very appropriate category based on the material assessment results, namely 87% from material expert validators I and 93% from material expert validators II. The results of students' responses to Gaman Raja were very good, namely the material aspect was 89%, the language aspect was 87%, the presentation aspect was 91%, and the graphic aspect was 97%.